2023
DOI: 10.54183/jssr.v3i1.193
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Marine Pollution: An Analysis of MARPOL 73/78 Regulations and Global Implementation Efforts

Abstract: This article discusses the regulations of MARPOL 73/78 for the prevention and control of pollution by garbage from ships and its implementation in various countries. MARPOL 73/78 was adopted in 1973 and is an international convention aimed at preventing and controlling pollution from ships. Annex V of the convention regulates the disposal of garbage from ships and requires ships to keep a garbage management plan on board. The article compares the participation and implementation of Annex V in different countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Several laws were put into place by MARPOL to limit the pollution produced by ships. These regulations focused on oil pollution, dangerous liquid chemicals, garbage, and air emissions [79], [80]. The futuristic IMPO plan for green shipping is depicted in Fig.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Several laws were put into place by MARPOL to limit the pollution produced by ships. These regulations focused on oil pollution, dangerous liquid chemicals, garbage, and air emissions [79], [80]. The futuristic IMPO plan for green shipping is depicted in Fig.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…The preliminary feasibility of a particular waste recycling technology [85] Pollution from ships-oil -Issues related to the identification and prevention of ship pollution, with special focus on oil pollution [86] -Issues related to pollution caused by oil spills into the sea, analyzing some major marine pollution incidents [87,88] -Various aspects of both land-and sea-based oil pollution [89] -Results of research based on a fact that over a million tons per year of oil is spilled from ships into the sea [90] -Adequacy level of the MARPOL convention implementation related to the pollution of the sea by oil from ships [91,92] Pollution from ships-solid and liquid waste -The marine pollution caused by marine domestic waste [93] -Issues related to the implementation of international regulations (mainly MARPOL convention) for the control of pollution of the sea with solid and liquid waste from ships [94][95][96][97] Pollution from ships-emissions -A fact that pollution from ships is not limited to the sea; it causes significant air and other forms of pollution [98] -The international regulations on ship emissions and their influence on level of SO 2 emissions from Ocean Going Vessels (OGVs) [99] -Summarizing studies that address air pollution, with special focus on particulate matter from marine vessels [100] -Pollution of air by large ships in the hub ports (taking into account that low-grade marine fuel oil contains 3500 times more sulfur than road diesel) [101] -Public health and climate impacts of low-sulfur fuels in global shipping [102] -The status of pollution mitigation measures implemented to date in the shipping sector [103] -The contributions of ship emissions of NO 2 , SO 2 , PM 10 , and PM 2.5 to air quality in the ports [104] -Annex VI (of the MARPOL convention) issues (influence of shipping industry on climate change) [105,106] -Initial strategy for the reduction in GHG emissions from ships in a port [107] -Air quality management in main Mediterranean ports [108] (Source: author).…”
Section: Research Problem Referencementioning
confidence: 99%
“…The research whose results are shown in the analyzed literature covers a very wide geographical area: developing countries [61,70], Indonesia [65], India [71], Nigeria [74,84], China [76], Malaysia [77], the world ocean [78,86], the Arctic region [80], Cambodia [89], Vietnam, the USA, Australia [94], the Southern North sea [99], Hong Kong [101], the Mediterranean sea [104,108], Kenya [105], and the Caspian sea [107]. Obviously, the references analyzed in Table 4, as per the related geographical areas, cover almost all continents and the world ocean and indicate what the priorities are in the domain of the prevention of pollution from ships in those areas.…”
Section: Research Problem Referencementioning
confidence: 99%
See 1 more Smart Citation